In-situ re-crystallization of heavily-irradiated Gd2Ti2O7. (1st August 2020) - Janish, Matthew T.; Schneider, Matthew M.; Valdez, James A.; McClellan, Kenneth J.; Byler, Darrin D.; Wang, Yongqiang; Chen, Di; Holesinger, Terry G.; Uberuaga, Blas P.
Abstract: Gadolinium titanate (Gd2 Ti2 O7, or GTO) and other lanthanide pyrochlores are interesting candidates for actinide waste disposal and fast ion conduction because the relevant material properties are intimately dependent on local cation structure. Therefore, a deep understanding of the kinetics associated with cation ordering and disordering is required if such material properties are to be tuned for specific device designs. To this end, single crystals of GTO were irradiated with 190 keV helium ions to a total fluence of 1 × 10 17 ions/cm 2, amorphizing the sample surface to a depth of 1 μm and resulting in significant He bubble accumulation. FIB lamellae lifted out from the irradiated sections were examined during heat treatment in the (scanning) transmission electron microscope. Two distinct stages of the re-crystallization of the amorphized material were observed. The material near the end of the ions' range transformed first and with the same orientation as the pristine material. This was due to the close proximity of the pristine material and the presence of small defect fluorite seeds, but the propagation of this growth front was frustrated by the large pores (formerly bubbles) in the He accumulation layer. This was followed by heterogeneous nucleation of new crystallites at random orientations at the top of the He accumulation layer, which is attributed to the high surface area associated with the many small He bubbles in that region. It is inferred that the kinetics of grain growth in this material are significantly faster than the kinetics of grain nucleation. Graphical abstract: Image, graphical abstract